Toolkit for evaluating the effectiveness of digital transformation of business models - Lomachynska, I.; Skoruk, A.; Liventsov, R. (Journal of Education, Health and Sport, 2026)
The article proposes an integral indicator of the digital readiness of the business model, the structure of which is based on a combination of four key sub-indices: technological development, competence, process and customer experience. On the basis of the proposed approach, a matrix of levels of digital maturity was formed, which allows identifying the current state of the enterprise and determining the strategic directions of digital transformation. A cyclical model of the formation of a digital strategy for the transformation of the business model has been developed, which ensures the consistency and continuity of digital changes. A methodical approach to evaluating the effectiveness of digital transformation has been improved by proposing a modified indicator of digital return on investment, which takes into account both direct economic and strategic effects of digitalization. A scenario forecast of the development of the business model depending on the pace of implementation of digital transformation has been developed, which includes optimistic, realistic and pessimistic options. For each of the scenarios, the expected results of digital changes are determined and practical recommendations are provided to increase the effectiveness of digital strategy implementation.